2017
DOI: 10.3141/2647-01
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Regional Characteristics on Injury Severity in Local Bus Crashes

Abstract: As the importance of public transportation increases, the management of bus-involved crashes has become a crucial issue for traffic safety. However, there are relatively few studies on crash severity for buses in South Korea. This study investigated factors that influence the severity of injuries that occur in local bus crashes. The study used commercial vehicle crash data from a 5-year period from 2010 through 2014 in South Korea. To determine unobserved regional effects on crash severity, a hierarchical orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 28 publications
3
25
0
1
Order By: Relevance
“…There is growing interest in the use of multi-level models to analyze hierarchically structured traffic crash data, and these models are often referred to as hierarchical models [1,[7][8][9][10][11][12][13][14][15]. Two research studies have summarized the use of multi-level analysis of traffic crash data and suggested further studies [14,15].…”
Section: Multi-level Models In Traffic Safetymentioning
confidence: 99%
See 4 more Smart Citations
“…There is growing interest in the use of multi-level models to analyze hierarchically structured traffic crash data, and these models are often referred to as hierarchical models [1,[7][8][9][10][11][12][13][14][15]. Two research studies have summarized the use of multi-level analysis of traffic crash data and suggested further studies [14,15].…”
Section: Multi-level Models In Traffic Safetymentioning
confidence: 99%
“…In this paper, we briefly described the specification of a two-level multi-level model. Yoon et al (2017) provided a detailed description of the model [1]. We applied a random intercept model that has been used extensively in previous studies.…”
Section: Two-level Multi-level Modelmentioning
confidence: 99%
See 3 more Smart Citations